2005
DOI: 10.1111/j.1523-1755.2005.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient education and access of ESRD patients to renal replacement therapies beyond in-center hemodialysis

Abstract: An incomplete presentation of treatment options is an important reason for under-utilization of home dialysis therapies and probably delays access to transplantation. Improvements in and reimbursement for pre-ESRD education could provide an equal and timely access for all medically suitable patients to various RRTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
248
3
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 275 publications
(263 citation statements)
references
References 31 publications
8
248
3
4
Order By: Relevance
“…Surveys (19) of US academic medical centers indicated that many training programs do not have sufficient number of patients or devote enough time for fellows to develop expertise in the care of PD patients; more than half of practicing nephrologists in the United States reported that they were trained mainly in providing care for MHD patients (20,21). Similarly, most incident dialysis patients reported that PD was not offered to them as a RRT (17,22). Surprising, the probability of offering PD as a method of treatment for ESRD was not related to the presence of medical contraindications to the therapy (17).…”
Section: Declining Use Of Pdmentioning
confidence: 99%
“…Surveys (19) of US academic medical centers indicated that many training programs do not have sufficient number of patients or devote enough time for fellows to develop expertise in the care of PD patients; more than half of practicing nephrologists in the United States reported that they were trained mainly in providing care for MHD patients (20,21). Similarly, most incident dialysis patients reported that PD was not offered to them as a RRT (17,22). Surprising, the probability of offering PD as a method of treatment for ESRD was not related to the presence of medical contraindications to the therapy (17).…”
Section: Declining Use Of Pdmentioning
confidence: 99%
“…In the United States, the growth of home modalities has been hindered by a system that has not until recently promoted home options to patients. 16 Despite the early success and implementation of home HD, use of this modality in that country declined rapidly in the years that followed the passage of the Social Security Act of 1972, legislation that favored facility HD rather than homebased care. 17 Meanwhile, in other countries, such as Australia and New Zealand, legislation and funding structures developed in a way to favor home-based care instead.…”
Section: Home Hemodialysis Uptakementioning
confidence: 99%
“…16,18 Such inertia is largely bred from unfamiliarity, as many physicians receive training that does not require experience with home HD. The unfortunate result is a lack of knowledge among physicians on how to establish home HD programs and how to adequately manage home HD training and care.…”
Section: Home Hemodialysis Uptakementioning
confidence: 99%
“…56 Multiple studies suggest that patients with chronic kidney disease may not receive adequate information to inform their treatment choices. [57][58][59] Information about treatment options is often provided to patients after vascular access is created (for one-third of patients, after dialysis has commenced), a timing problem that seems to strongly influence the choice of hemodialysis over other options. 60 Morton et al 60 suggest that understanding the factors that influence decision making can help inform patient education programs and enhance communication among providers, patients and families.…”
Section: Older Patients With Other Diseases: Decision Making In Nephrmentioning
confidence: 99%